Advancements in Applications of Manufacturing and Measurement Sensors - Yiping Shao; Shichang Du; Delin Huang (Sensors)
Manufacturing and measurement sensors are an integral part of advanced manufacturing technology, which requires sensors that can precisely capture and analyze various physical parameters during the manufacturing process [...]